Management predisposition, motives, opportunity and earnings management for fraudulent financial reporting / Suhaily Hasnan - Hasnan, Suhaily (2010)
This study investigates the factors that lead to the occurrences of fraudulent financial reporting. Specifically, this study examines the effect of predisposition (i.e. history of prior violations, related party transactions, and founders on the Board), motives (i.e. economic factor, ownership factors and political factor) and opportunity (i.e. poor corporate governance) on the occurrences of fraudulent financial reporting in Malaysia. In order to see the impact of predisposition, motives, opportunity and the occurrences of fraudulent financial reporting, 94 non-financial companies listed on Bursa Malaysia over the period 1996-2006, with complete data for predisposition, motives, and opportunity variables were selected. From the analysis conducted, the study finds that the corporate environment most likely to lead to an accounting fraud is characterized by factors that include'fewer related party transactions, higher number of prior violations, higher proportion of founders on the board, higher level of financial distress, higher level of cross directorship and lower audit quality. The study also finds that firms with family and foreign investors are less likely to have enforcement actions against them. Despite the general belief that greater independence of the board is associated with a lower incidence of fraudulent financial reporting, this study finds no evidence that level of board independence plays a role in the potential for fraudulent financial reporting. In addition, the study finds that political connection is not a determinant of fraudulent financial reporting in Malaysia. To the best of the researcher's knowledge, this study is the first to test whether the practice of earnings management may escalate to the level of accounting fraud. Interestingly, the study provides evidence that earnings management has a positive and significant relationship with fraudulent financial reporting. This confirms that the practice of earnings management, in addition to other governance variables, affects the probability of fraudulent financial reporting.